2024
DOI: 10.3390/ijms25010683
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Analyses Identify FKBP4 as a GBA1-Associated Protein in CSF and iPS Cells from Parkinson’s Disease Patients with GBA1 Mutations

Rika Kojima,
Wojciech Paslawski,
Guochang Lyu
et al.

Abstract: Mutations in the GBA1 gene increase the risk of developing Parkinson’s disease (PD). However, most carriers of GBA1 mutations do not develop PD throughout their lives. The mechanisms of how GBA1 mutations contribute to PD pathogenesis remain unclear. Cerebrospinal fluid (CSF) is used for detecting pathological conditions of diseases, providing insights into the molecular mechanisms underlying neurodegenerative disorders. In this study, we utilized the proximity extension assay to examine the levels of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Furthermore, PIT1 co-localized with TXNDC5 is required for ER homeostasis, chondrocyte survival, and skeletal development [197], also TXNDC5 knockdown is highly toxic to osteosarcoma cells, possibly implying that it has a critical function in cells that endogenously express collagen-I [198]. Other studies have identified an upregulation of TXNDC5 in Parkinson's disease, respiratory distress syndrome following cardiopulmonary bypass, COVID-19, malaria, Salmonella enteritidis and Marek's disease infection [199][200][201][202][203][204]. However, TNFRSF17 and TXNDC5 are the target genes for the COVID-19 vaccine [205].…”
Section: Txndc5 and Other Disordersmentioning
confidence: 98%
“…Furthermore, PIT1 co-localized with TXNDC5 is required for ER homeostasis, chondrocyte survival, and skeletal development [197], also TXNDC5 knockdown is highly toxic to osteosarcoma cells, possibly implying that it has a critical function in cells that endogenously express collagen-I [198]. Other studies have identified an upregulation of TXNDC5 in Parkinson's disease, respiratory distress syndrome following cardiopulmonary bypass, COVID-19, malaria, Salmonella enteritidis and Marek's disease infection [199][200][201][202][203][204]. However, TNFRSF17 and TXNDC5 are the target genes for the COVID-19 vaccine [205].…”
Section: Txndc5 and Other Disordersmentioning
confidence: 98%